2018
DOI: 10.1038/s41380-018-0307-y
|View full text |Cite
|
Sign up to set email alerts
|

WDR81 regulates adult hippocampal neurogenesis through endosomal SARA-TGFβ signaling

Abstract: Adult hippocampal neurogenesis, a process considered important for hippocampal function, is regulated at multiple molecular levels. Mutations in the gene encoding the WD40 repeat-containing protein WDR81 are associated with neurological disorders, including cerebellar ataxia, mental retardation, quadrupedal locomotion syndrome (CAMRQ2), and microcephaly. In this study, we show that ablation of WDR81 in adult neural progenitor cells (aNPCs) markedly reduced adult hippocampal neurogenesis and impaired hippocampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…Recently, Guo's group reported that loss of WDR81 in adult neural progenitor cells significantly reduced adult neurogenesis in hippocampus and impaired hippocampus-dependent learning [35]. Thus, this study supports our conclusion that WDR81 reduction is the one of the causes of neurodegenerative disorders.…”
Section: Plos Geneticssupporting
confidence: 90%
“…Recently, Guo's group reported that loss of WDR81 in adult neural progenitor cells significantly reduced adult neurogenesis in hippocampus and impaired hippocampus-dependent learning [35]. Thus, this study supports our conclusion that WDR81 reduction is the one of the causes of neurodegenerative disorders.…”
Section: Plos Geneticssupporting
confidence: 90%
“…Immunocytochemistry staining was carried out as described (Wang et al, 2018). Briefly, aNPCs were preblocked using PBS containing 5% normal goat serum (VECTOR, #S-1000) and 0.1% Triton X-100 for 30 min, followed by overnight incubation with primary antibodies.…”
Section: Tissue Preparation Immunohistochemistry and Immunocytochemistrymentioning
confidence: 99%
“…Neural Stem Cells (NSCs) In Vitro Assay Proliferation and differentiation analyses were performed as described previously (Wang et al, 2018). To study cell proliferation, we dissociated aNSCs with trypsin and plated them on poly-L-ornithin/laminin-coated slides (Nunc, #154526) at a density of 50,000 cells/well in proliferation medium.…”
Section: Tissue Preparation Immunohistochemistry and Immunocytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Our data point to the intracellular processing of EGFR as an important level of control for the regulation of proliferation in radial glial cells. WDR81 is likely to affect the trafficking of other cargos 40 , which may also impact cell radial glial cell proliferation. Moreover, the trafficking of neuronal cargoes, such as adhesion molecules, is likely to lead to the altered neuronal positioning observed in KO mice, and to the lissencephaly phenotype in human.…”
Section: Discussionmentioning
confidence: 99%